2013
DOI: 10.1007/s00281-013-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the aryl hydrocarbon receptor in the skin

Abstract: Among other functions, the skin serves as the barrier against the environment and provides vital protection from physical or chemical harm and from infection. Skin cells express the aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor and sensor of environmental chemicals; at the same time, AHR ligands are abundant in skin from exogenous or endogenous sources. For example, solar radiation, in particular ultraviolet (UV) B, generates AHR ligands from tryptophan in the skin. Recent evidence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
165
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(174 citation statements)
references
References 134 publications
3
165
0
3
Order By: Relevance
“…Furthermore, AhR-ROS-dependent regulation of IL-8 in normal human epidermal keratinocytes [60] and IL-6 in human sebocytes [61] by BaP provides a plausible explanation, at least in part, for why cigarette smoking exacerbates IL-8-related skin diseases such as psoriasis, palmoplantar pustulosis, and acne. In addition, the AhR signal pathway-induced Th17 differentiation and secretion of IL-17 and IL-22 as well as the interaction with estrogen may relate to the autoimmune skin diseases SLE and tuberous sclerosis [62][63][64], but the clinical correlation between them and EDCs is still uncertain.…”
Section: Inflammatory and Allergic Skin Diseasesmentioning
confidence: 99%
“…Furthermore, AhR-ROS-dependent regulation of IL-8 in normal human epidermal keratinocytes [60] and IL-6 in human sebocytes [61] by BaP provides a plausible explanation, at least in part, for why cigarette smoking exacerbates IL-8-related skin diseases such as psoriasis, palmoplantar pustulosis, and acne. In addition, the AhR signal pathway-induced Th17 differentiation and secretion of IL-17 and IL-22 as well as the interaction with estrogen may relate to the autoimmune skin diseases SLE and tuberous sclerosis [62][63][64], but the clinical correlation between them and EDCs is still uncertain.…”
Section: Inflammatory and Allergic Skin Diseasesmentioning
confidence: 99%
“…AhR is activated for example by environmental pollutants, mainly dioxins and PAHs, and takes part in the biochemical signaling cascade and toxic effects of these pollutants. It is also involved in processes such as cell growth, proliferation, and differentiation [13,30]. Tauchi et al (2005) showed that activation of the AhR in keratinocytes in transgenic mice caused inflammatory skin lesions and immunological imbalance, revealed as skin rashes and itches similar to those observed during atopic dermatitis [32].…”
Section: Activation Of the Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%
“…AhR is a ligand activated receptor, which is expressed in all types of cells in the skin and other tissues which are in contact with environmental factors, such as lungs or liver [30]. Its function is to support a cellular response for exogenous signals by regulation of cell homeostasis, activation of immune cells, and induction of xenobiotic metabolizing enzymes [30,31].…”
Section: Activation Of the Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%
See 1 more Smart Citation
“…AHR activity promotes their expansion and is obligatory for IL-22 production. AHR also encourages IL21 and IL23 output and inhibitory effects on Th17 [19]. The skin has several subsets of IL-17 producing cells.…”
Section: Introductionmentioning
confidence: 99%